Case reportNon-ST-elevation myocardial infarction after a wasp sting - Gawlik, Radoslaw; Pezold, Marcin; Bożek, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
We report a case of a 56-year-old woman with loss of conscious transferred to the cardiology unit where non-ST-elevation myocardial infarction was diagnosed. The patient reported a wasp sting a few minutes before the accident. The cardiac troponin level was high and confirmed damage of the heart muscle. Finally, echocardiography and myocardial perfusion scintigraphy revealed an ejection fraction of 50% with hypokinesia of posterior walls. Cardiac consequences of the insect venom sting are discussed in this article.